1996
DOI: 10.1126/science.274.5293.1704
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the Obesity Syndrome of ob/ob Mice by the Loss of Neuropeptide Y

Abstract: The obesity syndrome of ob/ob mice results from lack of leptin, a hormone released by fat cells that acts in the brain to suppress feeding and stimulate metabolism. Neuropeptide Y (NPY) is a neuromodulator implicated in the control of energy balance and is overproduced in the hypothalamus of ob/ob mice. To determine the role of NPY in the response to leptin deficiency, ob/ob mice deficient for NPY were generated. In the absence of NPY, ob/ob mice are less obese because of reduced food intake and increased ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
429
2
19

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 780 publications
(468 citation statements)
references
References 26 publications
18
429
2
19
Order By: Relevance
“…This was a surprising finding as it has previously been reported, and corroborated, although not significantly in both sexes in this particular study cohort, that DYNΔ mice actually display an antiobesity effect through decreased visceral and subcutaneous adiposity levels (Sainsbury et al, 2007). Moreover, NPY knockout mice have previously been shown to exhibit either unchanged food intake (Erickson et al, 1996a andHill andLevine, 2003), as well as unaltered body weight and/or adiposity levels (Erickson et al, 1996a andZengin et al, 2013), or in some circumstances, including leptin deficiency (Erickson et al, 1996b), reductions in fat mass (Baldock et al, 2009 andZengin et al, 2013). Indeed, in our current cohort of NPY knockout mice we observed no significant change from wildtype with respect to body weight or adiposity.…”
Section: Discussionsupporting
confidence: 89%
“…This was a surprising finding as it has previously been reported, and corroborated, although not significantly in both sexes in this particular study cohort, that DYNΔ mice actually display an antiobesity effect through decreased visceral and subcutaneous adiposity levels (Sainsbury et al, 2007). Moreover, NPY knockout mice have previously been shown to exhibit either unchanged food intake (Erickson et al, 1996a andHill andLevine, 2003), as well as unaltered body weight and/or adiposity levels (Erickson et al, 1996a andZengin et al, 2013), or in some circumstances, including leptin deficiency (Erickson et al, 1996b), reductions in fat mass (Baldock et al, 2009 andZengin et al, 2013). Indeed, in our current cohort of NPY knockout mice we observed no significant change from wildtype with respect to body weight or adiposity.…”
Section: Discussionsupporting
confidence: 89%
“…Results from diverse molecular and genetic paradigms are consistent with the implication that NPY, in concert with co-expressed orexigenic AgrP, GABA and adrenergic transmitters, constitutes an obligatory orexigenic signaling modality that is intimately involved in propagation of the timely appetitive drive under the direction of photoperiodic and hormonal cues (7,11,(27)(28)(29)47,(49)(50)(51)54,(56)(57)(58)(59). Additional recent disclosures that the hard wiring for the timely operation of this interplay is established during postnatal development have put the notion that NPY is a physiological appetite transducer on firm footing (11,(28)(29)(30)49,64).…”
Section: Is Npy a Naturally Occurring Appetite Transducer?supporting
confidence: 56%
“…15,16 Leptin, a signal of body adiposity, may promote longitudinal skeletal growth, since leptin-deficient obese (ob/ob) and diabetic (db/db) mice, with disrupted leptin signalling, display reduced linear growth. 17 Leptin may achieve this effect via direct effects on cartilage and bone 18,19 and also via CNS regulation of the somatotrophic axis. Several rodent studies have shown that chronic CNS administration of the potent orexigenic signal neuropeptide Y (NPY) inhibits the growth axis, 20,21 supporting a role for NPY in mediating linear growth.…”
Section: Introductionmentioning
confidence: 99%